The shoe-surface interaction during 180° change of direction with reduced approach steps on two different artificial turf surfaces - Clark, Colden Douglas, author; Reiser, Raoul F., II, advisor; Fling, Brett W., committee member; Labus, Kevin M., committee member (Colorado State University. Libraries, 2026)
Change-of-direction (COD) movements impose high traction and loading demands during early stance at the shoe–surface interface and are commonly associated with elevated lower-extremity injury risk. Third-generation (3G) artificial turf (AT) infill composition and commonly performed reduced approach strategies may influence shoe–surface interaction, yet their combined effects during high-demand COD tasks remain poorly understood. The purpose of this study was twofold: (1) to investigate loading and traction differences between 3G AT systems infilled with crumb rubber (CR) or engineered wood (EW), and (2) to evaluate how a 1-step versus 2-step approach influences shoe–surface interaction during a maximal-effort 180° COD. Twenty-one physically active athletes completed a minimum of six trials per condition across both surfaces and approach strategies. Three-dimensional kinematic and kinetic data were analyzed to quantify ground reaction forces (GRFs), loading rates, traction metrics, foot and body center-of-mass (COM) kinematics. Statistical analyses were performed using a linear mixed-effects model (LMM) to account for the repeated-measures design and within-subject variability. EW produced greater GRFs and loading rates than CR, accompanied by reduced initial foot displacement and lower horizontal foot velocity at initial contact. In contrast, CR demonstrated greater foot displacement and horizontal foot velocity, consistent with its greater reported compliance. Despite these differences, vertical foot velocity at initial contact and time to minimum foot velocity did not differ between surfaces, likely reflecting differences in impulse distribution, with higher forces applied over shorter displacement on EW and lower forces applied over longer displacement on CR. Participant perceptions aligned with COM and foot kinematics, with EW generally perceived as providing greater traction, evident by a more aggressive trunk lean angle and lower horizontal COM velocity angle. Despite these perceived differences, no surface-related differences were observed in traction metrics. The 2-step approach increased horizontal GRFs, vertical and horizontal loading rates, and linear traction coefficient relative to the 1-step approach, resulting in greater foot displacement following initial contact, while vertical GRFs remained unchanged. Participant feedback and COM mechanics indicated that the 2-step approach was more natural and aggressive, likely due to use of a penultimate step to prepare for the COD, whereas the 1-step approach required continued postural adjustment at initial contact. Rotational traction metrics did not differ between surfaces or approach conditions; however, a significant surface × approach interaction was observed for vertical free moment (VFM), with greater values during the CR 2-step condition, indicating increased rotational loading at the shoe–surface interface during higher-intensity CODs. Stiffer infill systems may constrain linear foot motion and enhance perceived stability but increase loading magnitude and rates, whereas more compliant infills permit greater foot displacement but may still expose athletes to elevated rotational loading specifically during higher intensity CODs. The overall results demonstrate that both infill type and reduced approach steps meaningfully influence the shoe–surface interaction during maximal effort 180° COD tasks and reinforce the need for human testing to capture performance and injury-relevant mechanics.
Keywords: BrockFill; crumb rubber; artificial turf; traction; change of direction